Resting metabolic rate varies by race and by sleep duration. (5th November 2015) - Spaeth, Andrea M.; Dinges, David F.; Goel, Namni
Abstract : Objective: Short sleep duration is a significant risk factor for weight gain, particularly in African Americans and men. Increased caloric intake underlies this relationship, but it remains unclear whether decreased energy expenditure is a contributory factor. The current study assessed the impact of sleep restriction and recovery sleep on energy expenditure in African American and Caucasian men and women. Methods: Healthy adults participated in a controlled laboratory study. After two baseline sleep nights, subjects were randomized to an experimental ( n = 36; 4 h sleep/night for five nights followed by one night with 12 h recovery sleep) or control condition ( n = 11; 10 h sleep/night). Resting metabolic rate and respiratory quotient were measured using indirect calorimetry in the morning after overnight fasting. Results: Resting metabolic rate—the largest component of energy expenditure—decreased after sleep restriction (−2.6%, P = 0.032) and returned to baseline levels after recovery sleep. No changes in resting metabolic rate were observed in control subjects. Relative to Caucasians ( n = 14), African Americans ( n = 22) exhibited comparable daily caloric intake but a lower resting metabolic rate ( P = 0.043) and higher respiratory quotient ( P = 0.013) regardless of sleep duration. Conclusions: Sleep restriction decreased morning resting metabolic rate in healthy adults, suggesting that sleep loss leads to metabolic changes aimed at conserving energy.